Zombie dan Diversifikasi Pada Masa Covid-19 - Michelle Fedora; Tan Ming Kuang (Politeknik Ganesha Medan, 2023)
The financial crisis has caused companies to compete to maintain their financial performance in order to avoid entering the category of